Team Accelerated Instruction, Initials and Problem-Solves Ability In Junior High School - Widodo, Sri Adi; Purnami, Agustina Sri; Prahmana, Rully Charitas Indra (International Journal on Emerging Mathematics Education, 2017)
This research aims to test the effectiveness of the Team Accelerated Instruction (TAI) towards the ability of the students to solve mathematics problems based on their initial ability. This study is an experiment with 367 students involved as the research sample taken using the cluster technique. The research variable is the problem-solving ability, the initial ability, and the learning model. Analysis of variance was used to analyze the data which leads to the conclusions that (1) the TAI is more effective than the Direct Instruction (DI); (2) the students having moderate initial ability performed better compared to the lower and the higher initial ability; (3) among the students with moderate initial ability, TAI was more effective to be used than DI; and (4) in the implementation of  TAI and DI, the problem solving ability of the students is relatively similar.